Parental knowledge, attitudes and beliefs regarding fever in children: an interview study - Kelly, Maria (BMC Public Health, 2016)
BACKGROUND: Fever is one of the most common childhood symptoms. It causes significant worry and concern for parents. Every year there are numerous cases of over- and under-dosing with antipyretics. Caregivers seek reassurance from a variety of sources including healthcare practitioners. The aim of this study was to describe parental knowledge, attitudes and beliefs regarding management of childhood fever in children aged 5 years and under. METHOD: Semi-structured interviews were conducted with 23 parents at six ante-natal clinics in the south west of Ireland during March and April 2015. The Francis method was used to detect data saturation and thereby identify sample size. Thematic analysis was used to analyse the data. RESULTS: Twenty-three parents participated in the study. Five themes emerged from the data: assessing and managing the fever; parental knowledge and beliefs regarding fever; knowledge source; pharmaceutical products; initiatives. Parents illustrated a good knowledge of fever as a symptom. However, management practices varied between participants. Parents revealed a reluctance to use medication in the form of suppositories. There was a desire for more accessible, consistent information to be made available for use by parents when their child had a fever or febrile illness. CONCLUSION: Parents indicated that further initiatives are required to provide trustworthy information on the management of fever and febrile illness in children. Healthcare professionals should play a significant role in educating parents in how to manage fever and febrile illnesses in their children. The accessible nature and location of pharmacies could provide useful support for both parents and General Practitioners.